Representation of Racial Disparity in Angie Thomas's The Hate U Give - Sari, Agnes Indriani; Kurniawan, Muhammad Hafiz (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
Racism has become the biggest social issue in the world because of its constant unjust treatment that affects people from minority races, ethnicities, and religions. Related to this issue, The Hate U Give conveys the social condition where racial disparity towards black people is profoundly represented in the narrative. This study focuses on identifying the ideational metafunction elements, including transitivity and ergativity patterns found in the narrative. It reveals how the racial disparity is performed by the use of the meta function. Mixed method research was employed to collect and analyze the data to yield more insightful information that complements both methodologies’ findings. The theory of Systemic Functional Grammar was used to identify and classify the ideational metafunction elements from the collected narrative, and the Discourse Analysis approach was applied as a theoretical approach to support the observation. The result concluded that in the analysis of transitivity patterns, material and relational processes dominate the narrative by approximately 25% to 33% of the entire collected narrative. The findings show that racial disparity in analyzing black people that was performed by law enforcement in the collected narrative is manifested in three forms: police brutality, racial profiling, and sentencing policy.